Tratamento descentralizado de efluente sanitário utilizando reator compartimentado anaeróbio/aeróbio - Perini, Barbara [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Pollution, waste and misuse of water resources in the world are important aspects to be evaluated. The lack of adequate sewage treatment and sanitation conditions may contribute to the proliferation of numerous diseases and cause degradation of water bodies. The proper disposal of sewage and its treatment, is essential for the protection of public health. An economically and technically feasible alternative to treatment of domestic sewage systems is the use of baffled reactors anaerobic/aerobic, because it promotes the removal of organic matter, the reduced need for oxygen in the aerobic chamber, reduces spending on electricity. According to exposed scenario, the present study aimed to evaluate of anaerobic baffled reactor / aerobic to treat of sanitary sewage of low organic load, operating in different TDHs (16.5 and 8.25 hours). The performance of the reactor was evaluated by physical-chemical analysis of the collected samples. The parameters pH, temperature, volatile acids, alkalinity, dissolved oxygen, COD, BOD, suspended solids, turbidity, true color, total and fecal coliforms were monitored. The results showed an average efficiency of removal of Chemical Oxygen Demand of 78%, Biochemical Oxygen Demand of 71% and Total Suspended Solids of 81%

mau uso, a poluição e o desperdício dos recursos hídricos no mundo são aspectos importantes a serem avaliados. A carência de condições apropriadas de saneamento básico e de tratamento de esgoto, podem causar degradação de corpos d'água e colaborar para a proliferação de várias doenças. Para a proteção da saúde pública, é importante o tratamento de esgoto adequado. Assim para sistemas de tratamento de esgoto doméstico, uma alternativa viável e econômica são os reatores compartimentados anaeróbio/aeróbio, que removem a matéria orgânica, além de que a menor necessidade de oxigênio na câmara aeróbia, reduz o gasto com energia elétrica. Desse modo, o presente trabalho teve como objetivo avaliar o desempenho e o comportamento do reator compartimentado anaeróbio/aeróbio, para tratar esgoto sanitário de baixa carga orgânica, operando em diferentes TDHs (16,5 e 8,25 horas). O desempenho do reator foi avaliado por meio de análises físico-químicas das amostras coletadas. Foram monitorados os parâmetros pH, temperatura, ácidos voláteis, alcalinidade, oxigênio dissolvido, DQO, DBO, sólidos em suspensão, turbidez, cor verdadeira, coliformes totais e fecais. Os resultados demonstraram uma eficiência média de remoção de Demanda Química de Oxigênio de 78%, Demanda Bioquímica de Oxigênio de 71% e Sólidos em Suspensão Totais de 81%
Keywords: Reatores quimicos; Quimica; Esgotos; Chemistry